Effects Of Positional Release Technique and Proprioceptive Neuromuscular Facilitation in Managing Piriformis Syndrome - Shaju, S.; Rekha, K. (Journal of Neonatal Surgery, 2025)
Piriformis syndrome is referred to the piriformis muscle abnormality that further compress the sciatic nerve. Given the growing number of piriformis syndrome cases, whose exact course of therapy is still unclear despite several studies and efforts, an effective treatment is still up for debate. Therefore, this study is to ascertain how well proprioceptive neuromuscular facilitation and positional release technique work for piriformis syndrome. Following the inclusion and exclusion criteria, 74 piriformis syndrome individuals were selected and into two groups: the positional release therapy group and the proprioceptive neuromuscular facilitation group. Hip range of motion, lower extremity functional scale, and numerical pain rating scale values were recorded before and after the intervention. For a total of four weeks, both groups received treatment three times a week. After then, the data were tallied and statistically examined. According to the findings of the Paired-t-test, both groups significantly improved their range of motion, LEFS, and pain reduction (p<0.01). The PNF group is more effective than the PRT group at reducing pain, increasing range of motion, and LEFS, according to the independent "t"test for post values between the groups in all variables except hip external rotation (p>0.5). Although both groups had a decrease in discomfort and an improvement in function, proprioceptive neuromuscular facilitation is a more effective treatment for piriformis syndrome compared to positional release approach.